Efficiency evaluation of an algistatic treatment based on barley straw in a hypertrophic pond - Prygiel, Emilie; Charriau, Adeline; Descamps, Romain; Prygiel, Jean; Ouddane, Baghdad; Billon, Gabriel (Journal of Environmental Engineering and Landscape Management, 2014)
Eutrophication processes were closely examined in a hypertrophic pond that was subjected to a barley straw treatment to inhibit cyanobacteria blooms. A phytoplankton activity was present from February to November 2010 with Chlorophyll a concentrations that ranged between 8 and 83 μg L-1 . The good oxygenation of the pond provided by primary production all along the year seems to maintain an oxic layer at the top of the sedimentary column. A high-frequency monitoring of algal development pointed out the end of the diatom bloom at the end of April and the growth of green algae from beginning of May. One month later, the development of cyanobacteria supplanted other algae several times. The implementation of barley straw does not seem to hinder the growth of cyanobacteria in June, August and September and do not promote the development of other algae potentially favoured by such a treatment. As a consequence, a barley straw treatment does not seem to be really appropriate for this kind of ponds in Northern France and more tests should still be undertaken to prove its real efficiency.